Simultaneous determine of Doppler shift and group delay time using amplitude modulated chirp-signal - Kolchev, A. A.; Nedopekin, A. E.; Shumaev, V. V. (НТУ "ХПІ", 2014)
New method of the simultaneous measurement of the frequency dependencies of Doppler shift and group delay time of separate ionosphere modes by means of amplitude modulated chirp signal is presented in this paper. The algorithms of data processing are presented.

Представлено новий метод одночасного вимірювання частотних залежностей допплерівського зсуву і часу групової затримки окремих іоносферних мод з використанням безперервного ЛЧМ сигналу з амплітудною модуляцією. Наведено порядок обробки даних під час вимірювання.
Keywords: ionosphere; chirp-sounder; phase; Doppler shift; іоносфера; ЛЧМ іонозонд; фаза; допплерівській зсув